The Effect of Specific Training Exercises Using Training Aids on the Development of Fast-Break Performance among Under-18 Three-on-Three Basketball Players - Zaid Mohammed Jabbar (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to examine the effect of specific strength training exercises using training aids on the development of three-player fast-break performance among under-18 basketball players. Materials and Methods: This study used an experimental method with a pre-test and post-test control group design. The research population consisted of basketball players from seven clubs in Dhi Qar Governorate, Iraq, during the 2025–2026 season. The sample was selected purposively from Al-Nasiriya Club players under 18 years old. A total of 30 players participated, with 10 players used for the pilot study and 20 players assigned to the main research sample, divided into experimental and control groups. The experimental group received specific strength training exercises using training aids, while the control group followed the regular training program. Data were collected through pre- and post-tests of three-player fast-break performance and analyzed using appropriate statistical procedures. Results: The results showed that the experimental group achieved greater improvement in three-player fast-break performance after applying the proposed strength training exercises with training aids. The training program helped improve movement coordination, transition speed from defense to offense, attacking organization, and scoring effectiveness during fast-break situations. Conclusions: Specific strength training exercises using training aids had a positive effect on developing three-player fast-break performance among under-18 basketball players. These exercises may be recommended for youth basketball coaches to improve fast-break execution, reduce random attacking movements, and enhance offensive effectiveness during competition.